Real Estate Due Diligence A Guideline for Practitioners (Management for Professionals,, 2018)
Due diligence is the bedrock of real estate deals, regardless of the volume of transaction. This book presents a comprehensive guide to understanding and implementing due diligence and making an accurate assessment of the risks. While this process has become a "no-brainer" for investment professionals, the market standard on this essential topic has not yet been laid out in a comprehensive form that covers all the major aspects of real estate due diligence: legal, tax, financial and technical issues. This book fulfils that need, and gives it a form that can be used for German, European, or even international transactions. Written in a reader-friendly fashion, the easily navigable chapters are organized into the four due diligence dimensions, with ample examples and key takeaways. Be they real estate investors, or a management students specializing in the asset class, this book is a core resource for anyone wanting to get to grips with due diligence.